An analytical study comparing the work done and the instantaneous speed of the ball to launch the penalty skill from the penalty mark (6 meters and 10 meters) for FUTSAL players - Dr. Diar Muhammed (الرياضة المعاصرة, 2020)
The importance of the research lies in trying to find the best solutions to get the player to the optimal motor path by studying mechanical (kinematical) variables for one of the most important skills for the futsal soccer game, which is the scoring skill of the penalty marks (6 - 10) meters in highlighting the study of the differences between The completed work and the instantaneous speed of the ball to launch the scoring skill from the penalty mark for scoring (6 meters and 10 meters) for players in some biomechanical variables such as the vertical work done variable and the angle of the ball launch so that we can know those differences and overcome them in the stages of education and training.